Environmental factors contributing to the development of brown muscle disease and perkinsosis in Manila clams (Ruditapes philippinarum) and trematodiasis in cockles (Cerastoderma edule) of Arcachon Bay. (8th July 2013) - Binias, Cindy; Tu Do, Van; Jude‐Lemeilleur, Florence; Plus, Martin; Froidefond, Jean‐Marie; de Montaudouin, Xavier
Abstract: The aim of the present study was to identify environmental factors that could explain the distribution of different pathologies of commercially exploited intertidal bivalves in an Atlantic lagoon, Arcachon Bay. In particular, the role of the salinity gradient as a driver was explored. The Manila clam Ruditapes philippinarum experienced two severe pathologies, perkinsosis, which is due to a protozoan parasite, and brown muscle disease (BMD), the etiological agent of which remains unknown. Perkinsus olseni infection was very low in a small low‐salinity area but, at the scale of the entire lagoon, was more influenced by organic matter content in the sediment and by emersion time. BMD prevalence was also 2.6 times higher in the higher organic content area but was also negatively correlated with salinity. The sympatric cockle ( Cerastoderma edule ) was affected by eight trematode species. These parasites have a complex life cycle that generally involves three free‐living host species. The distribution of the different trematode communities was rather patchy within Arcachon Bay with no clear relationship with measured environmental factors. The dominance of particular trematode species could be due to the presence of other hosts involved in their life cycle, making it more difficult to detect a major environmental driver. This survey demonstrated that salinity is not a major factor explaining disease distribution in this temperate lagoon. This result has consequences for the research of 'refuge areas' (free of diseases) or 'hot spots' (heavy infection) for species of high economic value.